2016
DOI: 10.1093/bioinformatics/btw709
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based re-engineering of ErbB signaling: a modeling pipeline for integrative systems biology

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Pogson et al also explored the NF‐κB signaling pathway via ABM and showed that they could capture the dynamics observed by real‐time single cell analysis . More recently, Das et al studied the ErbB signaling pathway . ErbB receptors are responsible for propagation of signals throughout the cell to regulate cell proliferation, differentiation, migration, adhesion, apoptosis, and embryogenesis.…”
Section: Examples Of Molecular Agent‐based Modelingmentioning
confidence: 99%
“…Pogson et al also explored the NF‐κB signaling pathway via ABM and showed that they could capture the dynamics observed by real‐time single cell analysis . More recently, Das et al studied the ErbB signaling pathway . ErbB receptors are responsible for propagation of signals throughout the cell to regulate cell proliferation, differentiation, migration, adhesion, apoptosis, and embryogenesis.…”
Section: Examples Of Molecular Agent‐based Modelingmentioning
confidence: 99%
“…ABM also has the advantage that it enables spatial relationships to be considered, whereas this is not easily done for equation-based methods. ABM has been used in many areas, including in sociology, town-planning and economics, but has only been applied to the study of receptors in a few instances, with a primary focus on the modelling of complex intracellular signalling pathways [ 15 , 16 ]. In ABM, it is relatively easy to incorporate rules that govern the clustering of receptors such as ligand binding, location, phosphorylation and interactions with other receptors and signalling molecules, and thereby study their interactions.…”
Section: Introductionmentioning
confidence: 99%